Anatomical localization of motor entry points of flexor digitorum superficialis - Theresa Susan Kuriakose; Mythraeyee Prasad; Sunil Jonathan Holla (Asian Journal of Medical Sciences, 2025)
Background: The knowledge about dense zones of motor entry points (MEPs) of muscles commonly involved in spasticity will be helpful for clinicians to inject the neurolytics into the ideal site. Aims and Objectives: The aim of the study was to identify the total number and dense zone of MEPs of flexor digitorum superficialis (FDS) and compare it will the vertical reference line. Materials and Methods: Thirty upper limbs from formalin-fixed cadavers were used. Proximal and distal MEPs to FDS were measured from the inter-epicondylar line. The dense zone of MEPs was identified and expressed in quartiles of the vertical reference line. Statistical analysis used: All analysis was done using Statistical Package for the Social Services software Version 21.0. Results: The ideal site for injecting neurolytic agents for FDS is in the second and third quartile of the vertical reference line from the inter-epicondylar line. Conclusions: Along with the guidance of ultrasound, neurolytic agents could be injected into the second and third quartile for FDS.